A novel flagellar sheath protein, FcpA, determines filament coiling, translational motility and virulence for the Leptospira spirochete - Wunder Junior, Elsio Augusto (2016)
National Institutes of Health. Brazilian National Research Council (CNPq). Welch Foundation.